PENGARUH GAYA HIDUP DAN ETNOSENTRISME KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN - Angkola, Marselina; Utami, Christina Whidya; Gosal, Gladys Greselda (PERFORMA, 2023)
"The Effect of Lifestyle and Consumer Ethnocentrism on Purchase Decisions of Baticue". This research which an title the influence of lifestyle and consumer ethnocentrism on purchase decision of Baticue. Independent variables in this research are lifestyle and consumer ethnocentrism. Dependent variable in this research is the purchase decision. This research is quantitative. The population in this research is 65 consumers who have ever done purchases in Baticue. The sampling method is saturated sampling. The respondents were obtained from online google form questionnaire. Data analysis in this research used SPSS version 22. The results of this research are lifestyle and consumer ethnocentrism have a significant positive effect on purchasing decisions.